2007
DOI: 10.1002/bmb.97
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of problem‐based learning on academic performance in genetics

Abstract: This study aimed at comparing the effectiveness of problem-based learning (PBL) 1 and traditional lecture-based instruction on elementary school students' academic achievement and performance skills in a science unit on genetics while controlling for their reasoning ability. For the specified purpose, two instructional methods were randomly assigned to intact classes of two different teachers. Each teacher had both PBL classes and traditional classes. Although students in PBL classes (n = 126) worked on ill-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 18 publications
0
19
0
2
Order By: Relevance
“…These include inheritance, reproduction, and meiosis (Bahar, Johnstone, and Hansell, 1999;Cavallo, 1996;Knippels 2002;Lewis and Leach, 2004;Lewis and WoodRobinson 2000;Schwartz and Lederman, 2004). Araz and Sungur (2007) declare annotated drawing a metacognitive strategy. There is an understanding with the efficacy of annotated drawing for meaningful science teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…These include inheritance, reproduction, and meiosis (Bahar, Johnstone, and Hansell, 1999;Cavallo, 1996;Knippels 2002;Lewis and Leach, 2004;Lewis and WoodRobinson 2000;Schwartz and Lederman, 2004). Araz and Sungur (2007) declare annotated drawing a metacognitive strategy. There is an understanding with the efficacy of annotated drawing for meaningful science teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature review, there can be seen many studies investigating the effect of PBL on science achievement (Araz & Sungur, 2007;Ayan, 2012;Filippatou & Kaldi, 2010;Lee & Tsai, 2004;Frank & Barzilai, 2004;Yalçın, Turgut & Büyükkasap, 2009). Ayan (2012) found that there was no significant difference between the achievement test post-test scores of experiment and control groups in the unit of light at fifth grade level.…”
mentioning
confidence: 99%
“…Ancak bu süreçte, öğrencilerin bilgi edinme açısından yetersiz kalacakları, öğretmenlerin alışkın oldukları otoritelerini ve kullandıkları öğretim stillerini bırakmakta isteksizlik yaşayabilecekleri, problem çözümünün beklenenden uzun ya da kısa sürmesi sonucunda oluşabilecek açıklığı öğretmenlerin iyi kontrol edememe durumunun olması, yöntemin bazı derslere uygulanmasında yaşanan sıkıntılar, kontrollü öğrenmenin olmaması sebebiyle her öğrencinin eşit akademik başarı düzeyine ulaşamayacağı gibi endişelerin ortaya çıktığı görülmektedir (Kaptan ve Korkmaz, 2001;Savery ve Duffy, 1995;Şenocak, 2005). Buna rağmen günümüze dek yapılmış ilgili çalışmalar incelendiğinde, öğrencilerin akademik başarılarını arttırabilmek için PDÖ'yi işe koşan bir çok çalışmanın yapıldığı görülmektedir (Araz ve Sungur, 2007;Demirel ve Arslan Turan, 2010;Deveci, 2002;Erdem, 2006;Kuşdemir, 2010;Özgen ve Pesen, 2008;Şendağ ve Odabaşı, 2009). Dağyar ve Demirel (2015) tarafından yapılan meta-analiz çalışmasında PDÖ'nin geleneksel öğretime kıyasla akademik başarıyı arttırma açısından yüksek düzeyde etkili olduğu sonucuna ulaşılmıştır.…”
unclassified